2006
DOI: 10.1111/j.1365-2648.2006.03808_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with breast cancer in newly diagnosed Iranian women

Abstract: Understanding how Iranian women cope with diagnosis of breast cancer is important to nurses involved in the process of healing. The majority of strategies used by Iranian women were positive, and religious faith played a major role in this. The findings of the study can be used to design a nursing approach to improve successful coping in Iranian women suffering from breast cancer, and can provide nurses and other healthcare professionals with deeper understanding of these women as they face this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
155
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(178 citation statements)
references
References 26 publications
19
155
0
4
Order By: Relevance
“…Although advances in current treatments dramatically increase the number of cancer survivors in recent years, fear of recurrence is still a main concern for cancer patients (Kim et al, 2012). The findings of some studies conducted in Iran also indicated fear of recurrence as one of the major concerns among Iranian cancer patients (Taleghani et al, 2006;Abdollahzadeh et al, 2014). It seems fear of recurrence negatively influence patients' perception of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Although advances in current treatments dramatically increase the number of cancer survivors in recent years, fear of recurrence is still a main concern for cancer patients (Kim et al, 2012). The findings of some studies conducted in Iran also indicated fear of recurrence as one of the major concerns among Iranian cancer patients (Taleghani et al, 2006;Abdollahzadeh et al, 2014). It seems fear of recurrence negatively influence patients' perception of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that married persons have a wider social network and receive high levels of support, especially from their spouse and children. In other studies, Iranian cancer patients consider their spouse and children as a main source for adaptation with cancer (Taleghani et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Es así como en un estudio colombiano las mujeres reportaron verse afligidas por la caída del cabello afectando su autoimagen y sintiéndose avergonzadas (30). Así mismo, en Irán, lo que más les preocupaba a las mujeres con cáncer y en quimioterapia eran los cambios físicos y de su imagen (31). Además, se señala que en investigaciones previas, las mujeres más jóvenes se ven más afectadas con la imagen corporal que las mujeres de más edad.…”
Section: Discussionunclassified